Risk and protective factors for falls on one level in young children: multicentre case-control study - Benford, P.; Young, B.; Coupland, C.; Watson, M.; Hindmarch, P.; Hayes, M.; Goodenough, T.; Majsak-Newman, G.; Kendrick, D. (BMJ Publishing Group Ltd, 2015)
Background: Childhood falls are an important global public health problem, but there is a lack of evidence about their prevention. Falls on one level result in considerable morbidity and they are costly to health services.